PMMB COVID-19 Bulletin: Spain (18th April 2020) - Hooi-Leng Ser; Vengadesh Letchumanan; Jodi Woan-Fei Law; Loh Teng-Hern Tan; Nurul-Syakima Ab Mutalib; Learn-Han Lee (Progress in Microbes and Molecular Biology)
The growing threat of pandemics around the world has contributed to rising uncertainty during various periods of age throughout history, with notable instances such as the Bubonic Plague in the sixth century caused by the pathogen Yersinia pestis, and more recently Middle East Respiratory Syndrome (MERS) caused by the coronavirus MERS-CoV in 2012. Fast forward to the last month of 2019, the WHO China Country Office was informed of pneumonia cases with unknown etiology, which later on determined a new type of coronavirus known as SARSCoV-2. Zooming into European countries, Spain is no stranger to coronavirus-related pandemics, given that this country was the first to publicly report the 1918 flu pandemic caused by the H1N1 coronavirus. Unfortunately enough, Spain is once again not spared from the current ordeal, recording the highest confirmed cases of COVID-19 (diseased caused by SARSCoV-2) in Europe, with cumulative cases of 190,839 and 20,002 deaths. The Spanish government has taken counter-measures for the management of COVID-19, consisting of the announcement of “state-of-emergency” and subsequent extension to control movements, setting up research grants to expedite drug and vaccine development in addition to introduction of the use of artificial intelligence as an official channel to provide advice and enquires about COVID-19. These are all part of a collective effort worldwide in alleviating dwindling healthcare resources in hopes of starving the virus of hosts by introducing travel restrictions and movement control as well as giving more time for a cure to be engineered. Through the advancement in technologies, improved trade, heightened human mobility and as well as the spurning of social media, we are able to closely monitor the latest progress of this pandemic; working together to remove the gloomy clouds before us will eventually lead to a solution of this pandemic.